Prostaglandin E2 inhibition of IL-27 production in murine dendritic cells: a novel mechanism which involves IRF1 - Hooper, Kirsten M (J Immunol, 2017)
IL-27, a multifunctional cytokine produced by antigen-presenting cells, antagonizes inflammation by affecting conventional dendritic cells (cDC), inducing IL-10, and promoting development of regulatory Tr1 cells. Although the mechanisms involved in IL-27 induction are well-studied, much less is known about the factors that negatively impact IL-27 expression. Prostaglandin E2 (PGE2), a major immunomodulatory prostanoid, acts as a pro-inflammatory agent in several models of inflammatory/autoimmune diseases, promoting primarily Th17 development and function. In this study, we report on a novel mechanism which promotes the pro-inflammatory function of PGE2. We showed previously that PGE2 inhibits IL-27 production in murine bone marrow derived DCs. Here, we show that, in addition to BMDCs, PGE2 inhibits IL-27 production in macrophages and in splenic cDC and we identify a novel pathway consisting of signaling through EP2/EP4→induction of cAMP→downregulation of IRF1 expression and binding to the p28 ISRE site. The inhibitory effect of PGE2 on p28 and irf1 expression does not involve endogenous IFNβ, STAT1 or STAT2, and inhibition of IL-27 does not appear to be mediated through PKA, EPAC, PI3K, or MAPKs. We observed similar inhibition of il27p28 expression in vivo in splenic DC following administration of dimethyl PGE2 in conjunction with LPS. Based on the anti-inflammatory role of IL-27 in cDC and through the generation of Tr1 cells, we propose that the PGE2-induced inhibition of IL-27 in activated cDC represents an important additional mechanism for its in vivo pro-inflammatory functions.